Synopsis of Clinonana Osborn (Hemiptera: Cicadellidae: Iassinae): new distributional records and description of a new species - Engel, Giulia; Takiya, Daniela Maeda (Zootaxa, 2012)
Based on the study of over 100 specimens, the apparently rare leafhopper genus Clinonana Osborn, 1938 is redescribed, newdistributional records are given, a new species is described, and a taxonomic key to all three species is given. The internalfemale genitalia of C. mirabilis (Spångberg, 1878) and C. impensa Kramer, 1966 are described and illustrated for the first timeand no diagnostic characteristics to distinguish females of these species were found. Clinonana impensa is newly recordedfrom Bolivia and Clinonana mirabilis is newly recorded from Bolivia, Peru, Suriname, and from the Brazilian states Amazo-nas, Maranhão, Mato Grosso, and Rondônia. Clinonana rafaeli sp. nov. is described from Rondônia (Brazil) and may be distin-guished from other Clinonana species because of the following characteristics: (1) pronotum width up to 1.8 times as broad asgreatest visible width of mesonotum; (2) styles in lateral view with ventral concavity in median portion; and (3) aedeagus preatrium with basal processes not extending to apex of shaft.